Pengaruh Kompensasi, Motivasi , Disiplin Kerja Terhadap Kepuasan Kerja Karyawan PT. Abadi Raya Commerce Balikpapan - Elok Fatoroni; Syahril Hasan; Tutik Yuliani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aimed to examine the impact of Compensation,Motivation, and Work Discipline on Job Satisfaction at PT Abadi Raya Commerce Balikpapan. The sample consisted of 52 employees, selected through purposive sampling and data collected via questionnaires. Data processing was conducted using Smart-PLS, analyzing outer and inner models, basic equations, and bootstrapping. The results indicate that Compensation,Motivation, and Work Discipline significantly influence Job Satisfaction at PT Abadi Raya Commerce Balikpapan.